Optimized border irrigation delays winter wheat flag leaf senescence and promotes grain filling - Yan, Feilong; Yu, Zhenwen; Shi, Yu (Frontiers in Plant Science, 2023)
Border irrigation is still the main irrigation method in the Huang-Huai-Hai Plain of China (HPC), and the suitable irrigation border length for water saving and high yield under traditional irrigation is still unclear. Therefore, a 2-year traditional border irrigation experiment (2017–2019) was conducted on the HPC. Four border lengths were tested: 20 m (L20), 30 m (L30), 40 m (L40), and 50 m (L50). These treatments were given supplementary irrigation at jointing and anthesis. An exclusively rainfed condition formed the control treatment. Compared with other treatments, the activities of superoxide dismutase antioxidant and sucrose phosphate synthetase, and the contents of sucrose and soluble proteins after anthesis were higher in the L40 and L50 treatments, while the content of malondialdehyde content was lower. Therefore, the L40 treatment effectively delayed the decrease in the soil plant analysis development (SPAD) value and chlorophyll fluorescence characteristics, promoted grain filling, and achieved the highest thousand-grain weight. Compared with the L40 treatment, the grain yields of the L20 and L30 treatment were significantly reduced, while the water productivity of the L50 treatment was significantly reduced. These findings suggest that 40 m was the optimal border length for both high yield and water saving in this experiment. This study provides a simple and low-cost water-saving irrigation method for winter wheat in the HPC under traditional irrigation, which can help alleviate the pressure of agricultural water use.